Managing Natural Resources for Sustainable Livelihoods : Uniting Science and Participation. - Pound, Barry (International Development Research Centre, 2003)
Drawing on extensive case studies, this book presents innovative approaches for participation and collective decision-making in natural resource management, good practice for research and challenges for future developments.